2022
DOI: 10.1002/1878-0261.13348
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of genomic breakpoints of ALK rearrangements in non‐small cell lung cancer

Abstract: ALK rearrangement is called the ‘diamond mutation’ in non‐small cell lung cancer (NSCLC). Accurately identifying patients who are candidates for ALK inhibitors is a key step in making clinical treatment decisions. In this study, a total of 783 ALK rearrangement‐positive NSCLC cases were identified by DNA‐based next‐generation sequencing (NGS), including 731 patients with EML4‐ALK and 52 patients with other ALK rearrangements. Diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…These conflicting results highlight the importance of validation assays such as RNA NGS for cases harbouring genomic intergenic‐breakpoint ROS1 rearrangements, to ensure the generation of an active chimeric protein. Moreover, unlike most of ALK and RET rare rearrangements which transformed into canonical fusions [ 22 , 23 ]. The two rare fusions in this study, CCDC6‐ROS1 and MYO5C ‐ ROS1 , were entirely consistent at the DNA and RNA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conflicting results highlight the importance of validation assays such as RNA NGS for cases harbouring genomic intergenic‐breakpoint ROS1 rearrangements, to ensure the generation of an active chimeric protein. Moreover, unlike most of ALK and RET rare rearrangements which transformed into canonical fusions [ 22 , 23 ]. The two rare fusions in this study, CCDC6‐ROS1 and MYO5C ‐ ROS1 , were entirely consistent at the DNA and RNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Here, ALK, ROS1, and RET fusion-positive cancer patients from the MSK-IMPACT Clinical Sequencing Cohort (MSKCC, CELL 2022) were used as the compared cohort [21]. The information of ALK and RET fusions in our cohort could be found in previous publications [22,23].…”
Section: Patients and Samplesmentioning
confidence: 99%
“…The EML4-ALK fusion consists of the basal domain encoded by the EML4 gene and the kinase region encoded by the ALK gene [39]. To date, numerous distinct ALK fusion partners, including EML4, Kinesin family member 5B (KIF5B), Kinesin Light Chain 1 (KLC1), and Translocated promoter region, nuclear basket protein (TPR), have been identified [40]. Among ALK-rearranged NSCLC, both the fusion partner and the EML4-ALK fusion variants have been considered candidate modifiers of transforming potential and response biomarkers to ALK-TKIs [41].…”
Section: Alk-tkismentioning
confidence: 99%
“…Interestingly, it has been suggested that individual genomic breakpoints of EML4 and ALK may have a different impact on the response to ALK-TKIs [40,52]. Nevertheless, a negative impact of TP53 mutations on PFS and OS, regardless of the EML4-ALK variant type (1 or 3a/b), was shown [45,44].…”
Section: Alk-tkismentioning
confidence: 99%